Upaya Peningkatan Kemampuan Membaca Al-Quran Santri Melalui Metode Ummi di Pesantren Pelajar Al-Fath Kediri - Mochamad Nasichin Al Muiz; Choiru Umatin (Edudeena : Journal of Islamic Religious Education, 2022)
Abstract: The Holy Qur'an is the revelation of Allah SWT which was gradually revealed to the Prophet Muhammad through the intermediary of the angel Jibril who was used as a guide for all mankind. Reading the Holy Qur'an is not only being able to read it, but also having to pay attention to the laws of tajwid, makhorijul letters, and the short length of reading the Holy Qur'an. The purpose of this research was to determine the implementation of the Ummi method of learning and the impact of learning using the Ummi method in an effort to improve the ability to read the Qur'an on the students of Al-Fath Rejomulyo Islamic boarding school of Kediri City. This researcher used descriptive qualitative research methods with data collection techniques by means of in-depth interviews, observations and documentation studies. The data analysis technique of this research is through the stages process of data reduction, data display and verification or conclusion. The results of the research carried out explain that the implementation of learning the Qur’an with the Ummi method has been carried out well, smoothly and an according to expectations. In addition, the reading of the Holy Qur’an of the students has improved very well with 7 stages, starting from the opening stage, apperception, concept planting, concept understanding, skill training and closing and is strengthened by the 10 pillars of the Ummi quality system. Abstrak: Kitab suci Al-Quran merupakan wahyu Allah SWT yang secara berangsur-angsur diturunkan kepada Nabi Muhammad SAW dengan perantara malaikat Jibril yang dijadikan petunjuk bagi seluruh umat manusia. Membaca Al-Quran tidak hanya sekedar bisa membacanya, namun juga harus memperhatikan hukum tajwid, makhorijul huruf, dan panjang pendek bacaan Al-Quran. Tujuan penelitian ini adalah mengetahui pelaksanaan pembelajaran metode Ummi dan dampak pembelajaran menggunakan metode Ummi dalam upaya meningkatkan kemampuan membaca Al-Quran pada santri pesantren pelajar Al-Fath Rejomulyo Kota Kediri. Peneliti menggunakan metode penelitian kualitatif deskriptif dean teknik pengumpulan data dengan cara wawancara mendalam, pengamatan dan studi dokumentasi. Teknik analisis data penelitian ini melalui tahapan proses reduksi data, display data dan verifikasi atau pengambilan kesimpulan. Hasil penelitian yang dilakukan menjelaskan bahwa pelaksanaan pembelajaran al-Quran dengan metode Ummi sudah terlaksana dengan baik, lancar dan sesuai harapan. Selain itu, bacaan Al Qur’an para santri mengalami peningkatan yang sangat baik dengan 7 tahapan, mulai dari tahap pembukaan, apersepsi, penanaman konsep, pemahaman konsep, latihan ketrampilan dan penutup serta diperkuat dengan 10 pilar sistem mutu Ummi.